1989
DOI: 10.1099/00222615-28-3-217
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of spores of Clostridium difficile altered by heat or alkali

Abstract: Summary. The effect of heating or alkali-treatment on spore recovery in ordinary growth medium was examined for four strains of Clostridium dificile. Heating spores at 80°C for 10 min produced 95-50-99-95% decreases in the recovery rates. Treatment with 0.1 N NaOH for 15 rnin produced 99-47 and 99.83% decreases in spore recovery rates for two of the four strains. The influence of either addition of lysozyme after treatment with sodium thioglycollate (thioglycollate-lysozyme method) or addition of sodium tauroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
(16 reference statements)
0
26
1
Order By: Relevance
“…The only other known approach to inducing germination of C. difficile in the laboratory is to treat spores with high concentrations of a reducing agent and lysozyme (16). This method of germination is not likely to be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only other known approach to inducing germination of C. difficile in the laboratory is to treat spores with high concentrations of a reducing agent and lysozyme (16). This method of germination is not likely to be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that taurocholate, a bile salt, enhances colony formation by C. difficile spores recovered from environmental surfaces and stool (2,40,44). Similarly, treatment of C. difficile spores with lysozyme and thioglycolate enhances colony formation (16,43). These effects on colony formation are clear, but it is difficult to discern what specific effects the treatments might have on germination.…”
mentioning
confidence: 99%
“…The germination receptors that C. difficile uses to sense the environment have not been identified. Based on homology searches, C. difficile germination receptors must be very different from known germination receptors (42), but they appear to be proteinaceous (13).…”
mentioning
confidence: 99%
“…C. difficile spores are stable at temperatures ranging from -20°C to 90°C [35]; they are resistant to desiccation [11•] and are only destroyed by high heat or alkaline pH [36]. A variety of cleaning agents are effective in killing the vegetative forms of C. difficile, but only chlorine-based disinfectants and high concentrations of vaporized hydrogen peroxide have been shown to be sporicidal [37].…”
Section: Infection Control and Preventive Measuresmentioning
confidence: 99%